Pengaruh Gameplay Mobile Legend: Bang Bang di Kalangan Mahasiswa AFI UIN-SU Medan dalam Tinjauan ‘Simulacra and Simulations’ Jean Baudrhillard) - Bungsu, Putri; Drajat, Amroeni; Ryandi, Ryandi (AHKAM, 2023)
In a review of Jean Baudrillard's "Simulacra and Simulations" the rise of the Mobile Legend Bang Bang game among Afi Uin-Su students. One of the many global games that are currently popular among students is Mobile Legend Bang Bang. Mobile Legend Bang Bang brings new colors to student society. This phenomenon of Mobile Legends game influence has a tendency to harm the young generation in a similar way to other addictive substances. The purpose of this study is to give a broad overview of the various factors that influence students' behavior who are Legend Bang Bang fans and to help them comprehend their significance as members of a "simulation society" in the context of Jean Baudrillard's analysis of simulacra and simulation. Field studies, a qualitative research methodology, are used by the author. Students at Afi UINSU are motivated by Mobile Legend Bang Bang because they are 1) curious and 2) stressed out after class and require fun, 3) monitor trends that are currently prevalent in the area, and 4) rate the game's difficulty accordingly. In the meantime, it appears that the case of the influence of the Mobile Legend Bang Bang games that is currently happening to student Afi Uin-Su is the outcome of technology advancements, as per the "Simulacra and Simulation" idea. Mobile Legend Bang Bang was made and developed to be engaging, so it has the potential to put Afi Uin-Su pupils to sleep and make them feel at home after playing it for a while.